ANALISIS KELAYAKAN USAHATANI CABAI MERAH KERITING (CAPSICUM ANNUM L.) DI DESA BONGKI LENGKESE, KECAMATAN SINJAI TIMUR - Nisa, Nur Haerun; Ahmad, Ahfandi; Megawati, Megawati; Nurdin, Fadilah (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2025)
This study aimed to analyze the income and feasibility of curly red chili farming in Bongki Lengkese Village, East Sinjai District, Sinjai Regency. The research employed a quantitative method using numerical data obtained from field observations to analyze production costs, revenue, income, and farming feasibility. The results showed that the average production cost of curly red chili farming was Rp. 3,508,071 per planting season. The average production reached 716.54 kg per season, generating an average total revenue (TR) of Rp. 17,792,090 per season. Based on this revenue and cost structure, the average net income (?) obtained by farmers was Rp. 14,284,019 per season. The feasibility analysis indicated that the R/C ratio was 5.07, meaning that every Rp. 1.00 of production cost generated Rp. 5.07 in revenue, resulting in a profit margin of Rp. 4.07. Therefore, curly red chili farming in Bongki Lengkese Village, East Sinjai District, Sinjai Regency is economically feasible and has good potential for further development.